2016
DOI: 10.1016/j.surg.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of the hospital and health care system characteristics in readmissions after major surgery in California

Abstract: Select hospital characteristics are associated with readmissions after major operative procedures. Because financial penalties may worsen performance in vulnerable or low-resource settings, policies aimed at reducing readmissions should be attentive to the potential unintended consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…With minimal access to physician services, it stands to reason that ongoing management of manageable comorbidities would degrade, resulting in rehospitalization. Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours . These hypothesis‐generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With minimal access to physician services, it stands to reason that ongoing management of manageable comorbidities would degrade, resulting in rehospitalization. Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours . These hypothesis‐generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are corroborated by others who have also found that patients with lower education levels, lower income, and increased distance from the hospital/rural location had a higher risk of rehospitalization, though the patient population studied was different from ours. 9,21,25,29,31,43 These hypothesis-generating findings need corroboration with prospective study to determine whether manipulating these variables affects outcomes. If indeed psychosocial and physician access postdischarge are major obstacles for patients and the only viable option for the patient becomes repeated inpatient treatment, then perhaps this would need to be accounted for before hospitals (in the United States) are financially penalized for rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the expectation that post-TKA aftercare at rehabilitation facilities is better than what could be provided at home. The relationship between higher procedure volume and better procedure outcome has been reported for TKA and other surgical procedures 5,45,46 , although the reasons for it remain opaque. Surgeon procedure volume may be a contributing factor 24,47 .…”
Section: Discussionmentioning
confidence: 96%
“…A lack of reliability of the collected data 3 as well as medicolegal and financial incentives to admit patients especially when surgery was performed in a different hospital are also limitations of this measure 4 . Furthermore, it remains uncertain whether readmission risk factors can be addressed in a manner that benefits patients 5 .…”
mentioning
confidence: 99%
“…Readmissions are increasingly being scrutinized by public insurers, accountable care 1 organizations, and the American College of Surgeons [1][2][3][4][5][6][7]. Trauma readmissions have been promoted as a quality indicator [2,5,8], and they have been used as a metric to compare patient care approaches and hospital outcomes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%